Management of pemphigus vulgaris: case report - Rahmaningsih, Widi; Santosa, Agus (Universitas Muhammadiyah Purwokerto, 2021)
Background: Pemphigus Vulgaris is an autoimmune disease attacking the skin and mucous membranes. This disease is considered a rare disease. Epidemiological data for Pemphigus Vulgaris in Indonesia remains limited, correspondingly, nursing management in this disease. This study aims to describe nursing management in patients with Pemphigus Vulgaris.Case presentation: a case of Pemphigus Vulgaris in a 28-year-old male was reported, with complaints of blisters all over his body appearing since 2019 and have not been completely recovered at the Banyumas General Hospital, Central Java, Indonesia.Conclusion: A combination of wound care, nutrition, vitamins, and pharmacology can accelerate the recovery of patients with Pemphigus Vulgaris